Asset Valuation with Incomplete Markets . - Boatsman, James R.; Baskin, Elba F. (The Accounting Review, 1981)
ABSTRACT: Estimating market values of assets in absence of an observable market price is a problem that arises often in accounting practice. Examples in the areas of taxation, capital budgeting, current cost accounting, and accounting for leases are discussed herein. A usable valuation scheme for such assets is derived from a modification of the popular two-parameter capital asset pricing model. Indirect empirical evidence is presented which suggests that the valuation scheme yields superior predictions to two competing schemes which have been advanced in the literature: indexing and earnings capitalization. In addition, limitations of the valuation scheme are discussed.